Lubricant skin on diverse biomaterials with complex shapes via polydopamine-mediated surface functionalization for biomedical applications - Kijun Park; Seunghoi Kim; Yejin Jo; Jae Park; Inwoo Kim; Sooyoung Hwang; Yeontaek Lee; So Yeon Kim; Jungmok Seo (Bioactive Materials, 2023)
Implantable biomedical devices require an anti-biofouling, mechanically robust, low friction surface for a prolonged lifespan and improved performance. However, there exist no methods that could provide uniform and effective coatings for medical devices with complex shapes and materials to prevent immune-related side effects and thrombosis when they encounter biological tissues. Here, we report a lubricant skin (L-skin), a coating method based on the application of thin layers of bio-adhesive and lubricant-swellable perfluoropolymer that impart anti-biofouling, frictionless, robust, and heat-mediated self-healing properties. We demonstrate biocompatible, mechanically robust, and sterilization-safe L-skin in applications of bioprinting, microfluidics, catheter, and long and narrow medical tubing. We envision that diverse applications of L-skin improve device longevity, as well as anti-biofouling attributes in biomedical devices with complex shapes and material compositions.